2015
DOI: 10.1128/microbiolspec.vmbf-0001-2014
|View full text |Cite
|
Sign up to set email alerts
|

Hijacking and Use of Host Lipids by Intracellular Pathogens

Abstract: Intracellular bacteria use a number of strategies to survive, grow, multiply, and disseminate within the host. One of the most striking adaptations that intracellular pathogens have developed is the ability to utilize host lipids and their metabolism. Bacteria such as Anaplasma , Chlamydia , or Mycobacterium can use host lipids for different purposes, such as a means of entry through lipid rafts, building blocks for bacteria membrane forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 236 publications
0
49
0
Order By: Relevance
“…Hijacking and utilization of host lipids are known for intracellular pathogens (reviewed in refs. [56][57][58][59]. For example, the closely related bacteria in the order Rickettsiales, Anaplasma phagocytophilum, hijacks cholesterol from NPC1-mediated LDLcholesterol vesicular trafficking pathways (60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hijacking and utilization of host lipids are known for intracellular pathogens (reviewed in refs. [56][57][58][59]. For example, the closely related bacteria in the order Rickettsiales, Anaplasma phagocytophilum, hijacks cholesterol from NPC1-mediated LDLcholesterol vesicular trafficking pathways (60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular bacterium Borrelia burgdorferi, the agent of tick-borne Lyme disease, also lacks LPS in its membrane (88). Instead, its membranes contain free cholesterol and cholesterol glycolipids that exist as lipid raft-like microdomains, and the growth of this spirochete requires an external cholesterol source (57,(89)(90)(91). Studies suggested that Borrelia encodes cholesterol modification enzymes to synthesize cholesterol glycolipids (92,93), and Borrelia membrane lipoproteins like OspA and OspB can interact with cholesterol lipids (89,94).…”
Section: Discussionmentioning
confidence: 99%
“…Given the evidence that [1] lipids are implicated in the pathogenesis and severity of Lyme disease and its complications [2], and the fact that elevated LDL and triglycerides are a significant risk factor (particularly in combination with inflammation) for cardiovascular disease, and [3] the documented risk of patients with Lyme disease for other atherosclerosis, ischemic strokes and carditis [17,18] and, [4] finally, the role of cardiometabolic disturbances, including obesity and dyslipidemia, may suppress innate immunity and allow neuroborreliosis [19,20]. These data clearly justify the need for further studies providing individualized and effective treatment for this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Borrelia bacteria recruit and metabolize host lipids that are essential for their growth and survival [1]. Therefore, Lyme disease caused by Borrelia burgdorferi requires cholesterol for survival of the microbe in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Many bacterial protein toxins, including VacA, are thought to utilize lipid rafts as the first step in the intoxication of host cells (27). To provide a direct measure of VacA's association with rafts, as well as to define features of the protein that mediate its affinity for raft versus nonraft domains, we analyzed VacA's phase preference using GPMVs.…”
Section: Discussionmentioning
confidence: 99%